Identification of serotype-specific T cell responses to highly conserved regions of the dengue viruses. - Malavige, G; McGowan, S; Atukorale, V; Salimi, M; Peelawatta, M; Fernando, N; Jayaratne, S; Ogg, G (2012)
Determining previous infecting dengue virus (DENV) serotypes has been difficult due to highly cross-reactive immune responses from previous DENV infections. Determining the correlates of serotype-specific immune responses would be crucial in understanding dengue transmission in the community and would also help to determine the correlates of protective immune responses. Therefore, we set out to define highly conserved, serotype-specific regions of the DENVs. Serotype-specific and highly conserved regions of the four DENV serotypes were identified using Basic Local Alignment Search Tool (BLAST) searches and custom perl scripts. Using ex-vivo and cultured enzyme-linked immunospot (ELISPOT) assays, we identified serotype-specific T cell epitopes within the four DENV serotypes in healthy adult donors from Sri Lanka. We identified T cell responses to 19 regions of the four DENV serotypes. Six peptides were from the NS2A region and four peptides were from the NS4A region. All immune donors responded to peptides of at least two DENV serotypes, suggesting that heterologous infection is common in Sri Lanka. Eight of 20 individuals responded to at least two peptides of DENV-4, despite this serotype not being implicated previously in any of the epidemics in Sri Lanka. The use of these regions to determine past and current infecting DENV serotypes will be of value to characterize further the dynamics of silent dengue transmission in the community. In addition, these T cell responses to these regions could be used to characterize DENV serotype-specific immune responses and thus possibly help us to understand the immune correlates of a protective immune response.